2018
DOI: 10.24075/brsmu.2018.061
|View full text |Cite
|
Sign up to set email alerts
|

Targeted sequencing in patients with clinically diagnosed hereditary lipid metabolism disorder and acute coronary syndrome

Abstract: The actual prevalence of genetic variants causing familial hypercholesterolemia (FH) in every population remains unknown. The aim of this work was to determine the spectrum of pathogenic variants in patients with acute coronary syndrome (ACS) and clinically diagnosed FH using targeted sequencing. We selected 38 patients with ACS from the sample of 2,081 participants of two multicenter observational studies (2004–2007; 2014–2016) who had a clinical diagnosis of FH based on the Dutch Lipid Clinic Network score a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
1
8
1
Order By: Relevance
“…This result is at variance with data from previous studies conducted in Russia and elsewhere in the world, showing that patients with LDLR mutations constitute the great majority (usually 70-80%) of cases with a hereditary background (Defesche et al, 2017). This discrepancy likely arose from the distinctive method of sampling and inaccuracy of the clinical FH diagnosis, making the results obtained (Averkova et al, 2018) incomparable with earlier data (Meshkov et al, 2009).…”
Section: The Ldlr Mutation Spectrum In Patients From Moscow With Fhcontrasting
confidence: 87%
See 2 more Smart Citations
“…This result is at variance with data from previous studies conducted in Russia and elsewhere in the world, showing that patients with LDLR mutations constitute the great majority (usually 70-80%) of cases with a hereditary background (Defesche et al, 2017). This discrepancy likely arose from the distinctive method of sampling and inaccuracy of the clinical FH diagnosis, making the results obtained (Averkova et al, 2018) incomparable with earlier data (Meshkov et al, 2009).…”
Section: The Ldlr Mutation Spectrum In Patients From Moscow With Fhcontrasting
confidence: 87%
“…New expectations of more efficient DNA-based diagnosis of FH have been raised by the introduction of targeted sequencing in routine practice. A recent study of 38 patients from Moscow with clinically diagnosed FH and acute coronary syndrome revealed genetic abnormalities in 24 individuals (63.2%) (Averkova et al, 2018); however, mutations in LDLR were found in only 10% of probands (four sequence variants, of which one (c.58G > A p.Gly20Arg) was experimentally demonstrated to be neutral). This result is at variance with data from previous studies conducted in Russia and elsewhere in the world, showing that patients with LDLR mutations constitute the great majority (usually 70-80%) of cases with a hereditary background (Defesche et al, 2017).…”
Section: The Ldlr Mutation Spectrum In Patients From Moscow With Fhmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these variants were unique but some LDLR variants occurred in several unrelated patients: p.Cys68Phe, p.Pro196Arg, p.Cys318Trp, p.Tyr375Asp and p.Ile566Phe. Of 35 variants previously described in the literature [ 6 , 7 , 8 , 9 , 10 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] only for the Russian population, six variants were also found in this study. Most of these variants were also unique, except for variant LDLR -p.Cys160Gly, that was found in six unrelated patients.…”
Section: Resultssupporting
confidence: 71%
“…The search strategy described above yielded 665 citations; 474 remained after duplicate removal. After the analysis of the abstracts referring to genetic testing or LDLR , APOB and PCSK9 variants in FH patients, 27 articles were selected, of which 25 contained data on the LDLR , APOB , and PCSK9 variants, including three of previously published articles by our group [ 6 , 7 , 8 , 9 , 10 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. These articles describe 91 causal variants of LDLR gene, one variant of APOB, and one variant of PCSK9 ( Figure 1 , Table A1 , Table A2 and Table A3 in Appendix A ).…”
Section: Resultsmentioning
confidence: 99%